2022
DOI: 10.56059/jl4d.v9i2.566
|View full text |Cite
|
Sign up to set email alerts
|

Mothers as Teachers: The New Role of Mothers in the New Normal

Abstract: The COVID-19 pandemic brought havoc to everyone but much more to child-rearing mothers. This qualitative study explored the new roles of mothers in the new normal specifically as being teachers to their children. Six mothers, who had public and private elementary grade children were purposely chosen. Information was gathered through a researcher-made validated interview questionnaire. Collection of information was done online through Facebook messenger and emails. Data analysis produced six themes, namely, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…All participants were residing in Digos City, Davao del Sur, Philippines. Due to this limitation, San Jose et al [7] mentioned that the findings of this study could not be applied to all parents who had children who attended public or private schools during COVID-19. The results only apply to the parents who took part in the study.…”
Section: Participants Of the Studymentioning
confidence: 94%
See 1 more Smart Citation
“…All participants were residing in Digos City, Davao del Sur, Philippines. Due to this limitation, San Jose et al [7] mentioned that the findings of this study could not be applied to all parents who had children who attended public or private schools during COVID-19. The results only apply to the parents who took part in the study.…”
Section: Participants Of the Studymentioning
confidence: 94%
“…However, Cahapay [6] pointed out several challenges that parents are experiencing with distance learning, such as difficulties in the teaching strategies, challenges in catching their children's motivation to learn effectively, and relational difficulties when children disobey. San Jose et al [7] added that parents needed to adjust the time, develop patience, and sacrifice for their children's education.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers aimed to understand how the intervention positively impacted students' learning experiences. In reference to [8], the primary aim of the qualitative method is to decipher the meaning of the experiences upon the evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…A mean range of 1.00-1.79 has a descriptive level as very low and has the interpretation that the assessment was never performed. [32] found that students got bored in their homes and demand a face-to-face set-up so that they could interact with others. It implies that students' direct learning does not mean being alone but it involves bond with other learners.…”
Section: Research Instrumentmentioning
confidence: 99%